'May she who was once beautiful be transformed into a monster': magic and witchcraft in Veneno es de amor la envidia (Madrid, 1711). (25th August 2020) - Acuña, Maria Virginia
Abstract: Through the lenses of magic, witchcraft and superstition, this article explores Veneno es de amor la envidia (Biblioteca Nacional de España, Ms. 19254), a little-known zarzuela by Sebastián Durón and Antonio de Zamora. I consider this zarzuela within its wider cultural context, looking at changing attitudes towards magic and witchcraft in early modern Spain, as well as within the context of Zamora's literary output. I propose that Veneno es de amor la envidia was intended to attract large crowds of theatregoers fascinated with depictions of the supernatural while also helping to debunk beliefs in witchcraft through the use of humour and parody. An examination of this rather intriguing zarzuela contributes to our understanding of an often-overlooked corpus of theatrical music of the Baroque.